Emerging Roles of circRNA Related to the Mechanical Stress in Human Cartilage Degradation of Osteoarthritis - Qiang Liu; Xin Zhang; Xiaoqing Hu; Lan Yuan; Jin Cheng; Yanfang Jiang; Yingfang Ao (Elsevier, 2017)
Circular RNAs (circRNAs) are involved in the development of various diseases; however, knowledge on circRNAs in osteoarthritis (OA) is limited. This study aims to identify circRNA expression in different regions affected by OA and to explore the function of mechanical stress-related circRNAs (circRNAs-MSR) in cartilage. Bioinformatics was employed to predict the interaction of circRNAs and mRNAs in the cartilage. Loss-of-function experiments for circRNAs-MSR were performed in vitro. A total of 104 circRNAs were differentially expressed in damaged versus intact cartilage. Of these circRNAs, 44 and 60 were upregulated and downregulated, respectively, in the damaged tissue. circRNA-MSR expression increased under mechanical stress in chondrocytes. circRNAs-MSR were silenced using small interfering RNA, and knockdown of circRNAs-MSR could suppress tumor necrosis factor alpha (TNF-α) expression and increase extracellular matrix (ECM) formation. Our results demonstrated that circRNAs-MSR regulated TNF-α expression and participated in the chondrocyte ECM degradation process. We propose that the inhibition of circRNAs-MSR could inhibit the degradation of chondrocyte ECM and knockdown of circRNAs-MSR could be a potential therapeutic target for OA.